Chiral metal-organic frameworks incorporating nanozymes as neuroinflammation inhibitors for managing Parkinson’s disease - Jiang, Wei; Li, Qing; Zhang, Ruofei; Li, Jianru; Lin, Qianyu; Li, Jingyun; Zhou, Xinyao; Yan, Xiyun; Fan, Kelong (Nature communications, 2023)
Nanomedicine-based anti-neuroinflammation strategy has become a promising dawn of Parkinson’s disease (PD) treatment. However, there are significant gaps in our understanding of the therapeutic mechanisms of antioxidant nanomedicines concerning the pathways traversing the blood-brain barrier (BBB) and subsequent inflammation mitigation. Here, we report nanozyme-integrated metal-organic frameworks with excellent antioxidant activity and chiral-dependent BBB transendocytosis as anti-neuroinflammatory agents for the treatment of PD. These chiral nanozymes are synthesized by embedding ultra-small platinum nanozymes (Ptzymes) into L-chiral and D-chiral imidazolate zeolite frameworks (Ptzyme@L-ZIF and Ptzyme@D-ZIF). Compared to Ptzyme@L-ZIF, Ptzyme@D-ZIF shows higher accumulation in the brains of male PD mouse models due to longer plasma residence time and more pathways to traverse BBB, including clathrin-mediated and caveolae-mediated endocytosis. These factors contribute to the superior therapeutic efficacy of Ptzyme@D-ZIF in reducing behavioral disorders and pathological changes. Bioinformatics and biochemical analyses suggest that Ptzyme@D-ZIF inhibits neuroinflammation-induced apoptosis and ferroptosis in damaged neurons. The research uncovers the biodistribution, metabolic variances, and therapeutic outcomes of nanozymes-integrated chiral ZIF platforms, providing possibilities for devising anti-PD drugs. The treatment of Parkinson’s disease (PD) is hampered by the lack of effective blood–brain barrier (BBB) traversing drugs. Here, the authors report nanozyme-integrated metal-organic frameworks with antioxidant activity and chiral-dependent BBB transendocytosis as anti-neuroinflammatory agents for PD treatment.